Main entrance to the Aga Khan Maqbara complex - Mumbai Archive Project Team (Jio Institute, 2024)
The main entrance to the Aga Khan Maqbara complex is accessed through a gateway on Dr Mascarenhas Road. Previously known as Eden Hall, it was renamed Hasanabad (inscribed at the entrance) in memory of Hasan Ali Shah, officially titled Aga Khan I.